"Developing human capitals in today's entrepreneurs: a practitioner perspective". Issue 4 (6th July 2020) - Murray, Alan; Palladino, Rosa
Abstract : Purpose: The main objective of this exploratory study is to analyze the range of human capitals necessary for the modern entrepreneur and the nature of the barriers to effectively support the development of these capitals. Human capital is one of the three dimensions of intellectual capital and this document examines the role of education and training for entrepreneurial success. Design/methodology/approach: Drawing on a broad review of the main contributions to research and practice in the field of intellectual capital and entrepreneurship issues, we conducted a qualitative study using semi-structured in-depth interviews on a sample of 10 professionals expert in business support. They represent a cross section of the main corporate agencies in Scotland. In addition, an interview guide was used to ensure that some questions, or "key questions", were asked to all participants, also allowing for the flexibility to obtain updated information. Findings: The interviews identified 21 key human capitals needed by today's entrepreneurs. However, the study also identifies the existence of obstacles to providing effective support for the development of human capital in the entrepreneur in terms of attention, process and resources. Research limitations/implications: Research limitations–The study is based on data collected by a sample of 10 professionals, according to a qualitative approach that focuses on a specific social field and therefore the results cannot be immediately generalized to other fields. Practical implications: Practical implications–The study identifies the key human capital needed to run a successful company, directing the professional to direct support interventions more effectively in order to increase productivity and improve success rates for its customers. Social implications: The value the long-term benefits of even a marginal increase in the efficiency of enterprise support to business through targeted entrepreneurial learning cannot be overstated. Originality/value: There is a lack of empirical data linking the development of human capital and entrepreneurship. This work has resonance for providers of enterprise support seeking to remain relevant to the entrepreneurial development needs of the entrepreneur.